Long-Term Outcomes of Nasopharyngeal Carcinoma in 148 Children and Adolescents. Issue 17 (April 2016) - Lu, Suying; Chang, Hui; Sun, Xiaofei; Zhen, Zijun; Sun, Feifei; Zhu, Jia; Wang, Juan; Huang, Junting; Liao, Ru; Guo, Xiaofang; Lu, Lixia; Gao, Yuanhong
Abstract : Abstract: The aim of this study was to investigate the survival and long-term morbidities of nasopharyngeal carcinoma (NPC) in children and adolescents. We retrospectively reviewed children and adolescents with NPC treated at Sun Yat-sen University Cancer Center from February 1991 to October 2010, where the prognostic factors and long-term effects of therapy were analyzed. A total of 148 patients were identified. The median age was 15 years old (range, 5–18 years) and the male to female ratio was 3.6:1. Most of the tumor histopathology was undifferentiated nonkeratinizing carcinoma (97.3%). The number of patients staged with IVa, IVb, IVc, III, and II were 45 (30.4%), 12 (8.1%), 5 (3.4%), 70 (47.3%), and 16 (10.8%), respectively. For the whole series with a median follow-up of 81 months (range, 6–282 months), the 5-year overall survival (OS) and disease-free survival (DFS) ratios were 79.3% and 69.7%, respectively. We observed significant differences in the 5-year OS (81.1% vs 25.0%, P = 0.002) and the DFS rates (72.2% vs 0.0%, P = 0.000) between patients with stage II to IVb disease and stage IVc disease. For patients with stage II, III, IVa, and IVb disease, we found a high radiation dose (dose > 66 Gy to the primary lesion) would not significantly improve the survival compared to the sub-high radiation dose group (dose = 60–66 Gy to the primary lesion), even considering the type of radiation therapy technologies. However, the incidences of sequelae (grades I–IV) in patients with high radiation dose were apparently higher than those in patients with low radiation dose. Considering the late sequelae, a dose of 60 to 66 Gy to the primary lesions seems to be enough for children and adolescents with NPC.